Mobile dynamically reformable formations for efficient flocking behavior in complex environments - Sahin, Turker; Zergeroğlu, Erkan (IEEE, 2008)
In this work inspired by flocking of birds or fish communities traveling together in the nature, we have developed a novel dynamically reformable mobile formation algorithm for the navigation of wheeled mobile robot (WMR) groups operating in complex and/or obstacle dense environments. The proposed method is formed via the combination of simple and computationally efficient tools such as (i) a mobile network of a small number of WMR sensors for detecting obstacles; (ii) Cardinal Cubic splines or Least Squares fits for modeling the formation boundaries based on this small network; and (iii) reference frames to ensure uniform spacing and velocity profiles along the ensemble. By these components a simple geometrical formation is developed for real time flock path planning of relatively large groups of small agents. To our best knowledge the proposed approach is novel and its effectiveness is verified by simulations in complex environments.
IEEE International Conference on Robotics and Automation -- MAY 19-23, 2008 -- Pasadena, CA